Perineural dexmedetomidine effects on sciatic nerve in rat - Yektaş,Abdulkadir (2017)
Abstract The present study was designed to test the hypothesis that high dose dexmedetomidine would increase the duration of antinociception to a thermal stimulus in a rat model of sciatic nerve blockade without causing nerve damage. The rats were anesthetized with isoflurane. After electromyography (EMG) recordings, right sciatic nerves were explored and perineural injections were delivered: Group D (n = 7), 40 µg µg kg-1 dexmedetomidine administration, Group II (n = 6), (0.2 mL) saline administration, Group III (n = 2), only surgically exploration of the right sciatic nevre. Time to paw withdrawal latency (PAW) to a thermal stimulus for both paws and an assessment of motor function were measured every 30 min after the nerve block until a return to baseline. The compound muscle action potential (CMAP) of right and left sciatic nerves were recorded 10 times per each nerve once more after perineural injections at 14 day. After EMG recordings, right and the part of left sciatic nerve were excised at a length of at minimum 15 mm for histopathological examination. Comparison of right/left CMAP amplitude ratios before and 14 days after the procedure showed a statistically significant difference (p = 0.000). There were no differences in perineural inflammation between the Group D, Group S, and Group E at 14 days.